2019
DOI: 10.1002/cta.2622
|View full text |Cite
|
Sign up to set email alerts
|

An accurate and simplified small signal parameter extraction method for GaN HEMT

Abstract: Summary In this paper, development of a small signal model for 2 × 200 μm GaN HEMT based on the conventional 20‐element model is presented. The proposed model presents a direct parameter extraction algorithm, instead of the hybrid optimization approach, that provides simplification, accuracy, and less computational complexity. The extrinsic elements are extracted using a modified cold pinch‐off condition while discarding the unwanted forward biasing of the gate. The negative drain to source capacitance Cds is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 28 publications
0
18
0
Order By: Relevance
“…In order to increase attention for high‐temperature and high‐power applications at high frequencies, the kink effects are investigated in the output reflection coefficient (S 22 ) and the short‐circuit current gain (h 21 ) to be shown how these phenomena affect the applications of electronic devices . At first, the S parameters are analyzed completely that S 11 and S 22 on Smith charts and S 21 and S 12 on polar plots are reported . The S parameters are investigated from 1 KHz to 100 GHz at V DS = 20 V and V GS = −1.5 V and as it is shown that the kink effect has the impressive influence on all the S parameters in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…In order to increase attention for high‐temperature and high‐power applications at high frequencies, the kink effects are investigated in the output reflection coefficient (S 22 ) and the short‐circuit current gain (h 21 ) to be shown how these phenomena affect the applications of electronic devices . At first, the S parameters are analyzed completely that S 11 and S 22 on Smith charts and S 21 and S 12 on polar plots are reported . The S parameters are investigated from 1 KHz to 100 GHz at V DS = 20 V and V GS = −1.5 V and as it is shown that the kink effect has the impressive influence on all the S parameters in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…|y meas − y predicted | y meas × 100. (19) The calculated MRE shows very less error within the range of training frequency (upto 13 GHz), and a rise in spike from 2-5% at the the start of extrapolation set before the error starts decreasing and curve settles down. Altogether, with the mean relative error varying between 1.5-3.5% for extrapolation set shows a very promising accuracy of the proposed model.…”
Section: Model Validationmentioning
confidence: 85%
“…This section investigates the reliability and effectiveness of the trained model by subjecting the model to novel set of inputs for broad frequency range from 1-18 GHz (with the frequency extrapolation) including noise and without noise utilizing one-third of measured data reserved for testing and validation purpose. To study the accuracy of the model more precisely, the prediction ability of the proposed model is enumerated in terms of mean relative error (MRE), expressed in (19), where y meas is the measured value and y predicted is the predicted value of the response variable of the proposed model. The relative error is plotted against the whole frequency range for four different set of multi-bias and different operating region of the transistor under noiseless condition as depicted in Fig.…”
Section: Model Validationmentioning
confidence: 99%
“…Next, de‐embedded S ‐parameters of the HEMT device is delivered to a small‐signal modeling process to investigate the influence of residual error on model parameters extraction. The modeling process is quite similar with well‐developed method for HEMT devices in literature, but it starts simply from intrinsic topology of the small‐signal model illustrated in Figure . Y ‐parameters of the intrinsic equivalent circuit can be simply expressed as y11=YGS+YGD y12=YGD y21=gmexp()italicjωτ1+italicjωCgsRiYGD y22=YDS+YGD where Y GS , Y GD , and Y DS are passive admittances of corresponding branch, YGS=1Ritalicgs+ω2Cgs2Ri+italicjωCgs1+ω2Cgs2Ri2 YGD=1Ritalicgd+ω2Cgd2Rj+italicjωCgd1+ω2Cgd2Rj2 Y…”
Section: De‐embedding Errors and Its Influence On Model Extractionmentioning
confidence: 99%